(Ri)pensare il calcio: una sfida per la filosofia contemporanea - Mario Tirino (SHARE Press, 2021)
This paper examines two volumes dedicated to the philosophy of football. The analysis of Bernhard Welte’s volume, which collects two of his essays, focuses on two aspects of his philosophy of football. On the one hand, Welte conceives football as a metaphor for life as a regulated combat. On the other, the German philosopher sees in football a link to myth. The analysis of Del Bò and Santoni de Sio’s work, on the other hand, brings out the many philosophical questions that the game of football raises (the role of luck, fair play, refereeing, etc.). From the point of view of promoting dialogue between disciplines, the philosophy of football can ultimately offer very fertile research ideas for the social sciences as well.